International commercial arbitration : contemporary problems confronting its effective use in dispute resolution - Saprudin Hj. Mohd Sharif (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2010)
The emergence of international commercial arbitration as an important method of resolving disputes reflected wide dissatisfaction with the traditional adjudicative method of resolving disputes. Excessive delays in the judicial system, expense of litigation, inapplicability of national laws to transnational disputes and uncertainty of outcome are some of the maladies associated with litigation. However, in the last twenty years there is an increasing concern over the judicialization of international commercial arbitration characterize by an increasingly legalistic and formality associated with delays and increased costs. It often resembles American style litigation with more procedural complexity and formality similar to litigation in national courts and subject to greater court intervention. International commercial arbitration has also been affected by an increasing modernization of national arbitration legislation in many states including Malaysia. This is due in part to the promulgation in 1985 of the UNCITRAL Model Law. Inevitably, under the national arbitration legislation, national courts at the place of arbitration may exercise supervisory powers over the international commercial arbitration conducted within the jurisdiction. States are also empowered to recognize and enforce the validity of the awards rendered in an international commercial arbitration. National courts may refuse to recognize or enforce the awards at the stage of recognition and enforcement. National courts involvement in the arbitral process therefore posed the biggest challenge to the autonomous nature of international arbitration. Innovations in telecommunications and global computer networks have also allowed for international commercial arbitration to be conducted in 'cyberspace'. This rapid development of 'cyberspace arbitration' or 'online arbitration' poses various jurisdictional and governance challenges for the current regime of international commercial arbitration. It is imperative that the continued recognition and acceptance of international commercial arbitration as a dispute resolution mechanism will ultimately depend on its ability to remain effective. Close scrutiny of the Islamic Law of Arbitration – Tahkim reveals that it can provide solutions to problems encountered in modern international commercial arbitration.